Medical Pluralism, Mainstream Marginality or Subaltern Therapeutics? Globalisation and the Integration of 'Asian' Medicines and Biomedicine in the UK. (January 2020) - Cant, Sarah
Abstract: Medical Pluralism refers to the coexistence of differing medical traditions and practices grounded in divergent epistemological positions and based on distinctive worldviews. From the 1970s, a globalised health market, underpinned by new consumer and practitioner interest, spawned the importation of 'non-Western' therapeutics to the UK. Since then, these various modalities have coexisted alongside, and sometimes within, biomedical clinics. Sociologists have charted the emergence of this 'new' medical pluralism in the UK, to establish how complementary and alternative medicines have fared in both the private and public health sectors and to consider explanations for the attraction of these modalities. The current positioning of complementary and alternative medicines can be described as one of 'mainstream marginality' (Cant 2009, The New Sociology of the Health Service, London: Routledge): popular with users, but garnering little statutory support. Much sociological analysis has explained this marginal positioning of non-orthodox medicine by recourse to theories of professionalisation and has shown how biomedicine has been able, with the support of the state, to subordinate, co-opt and limit its competitors. Whilst insightful, this work has largely neglected to situate medical pluralism in its historical, global and colonial contexts. By drawing on post-colonial thinking, the paper suggests how we might differently theorise and research the appropriation, alteration and reimagining of 'Asian' therapeutic knowledges in the UK.